The Effect of TIG Welding for 304 and 304L Stainless Steel to Mechanical Properties, XRD and EDX Characterization as Pressure Vessel Materials - Vuri Ayu Setyowati; Eriek Wahyu Restu Widodo (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2017)
The aim of this paper is to analyze the effect of TIG welding for Austenitic Stainless Steel type 304 and 304L as pressure vessel materials. These materials have different carbon content. 304 SS and 304L SS of 6mm metal sheet were used as observed materials. The groove angel for welded specimens is 60o and TIG welding current is 100A. Current and voltage for welding process are set constant. For analyzing mechanical properties, tensile test was used to calculate the yield strength, tensile strength, and elongation. X-Ray Diffraction (XRD) and X-Ray Spectroscopy (EDX) test were used to analyze the phase and element compositions, respectively. The tensile strength of welded 304 SS was decrease to 425,64 MPa compared to 304 SS which is 466,67 MP to 422,22 MPa. The highest elongation of 22% among to welded 304L SS and it has good ductility. Based on, XRD measurements, all specimens have austenite peaks but 304L SS and welded 304L SS have δ-ferrite peaks. EDX measurement was also used to explain the element composition supporting mechanical properties.